The disciplinary liability of Lithuanian lawyers : a comparative approach - Gruodyte, Edita (Baltic journal of law & politics, 2014)
The article presents basic findings about courts of honor in Lithuania. The data about disciplinary violations in five legal professions-judges, lawyers, prosecutors, notaries, and bailiffs-was obtained while implementing a scientific project on certain issues of legal ethics. The article provides data on the following issues: subjects initiating disciplinary cases; the number of cases for each legal profession; decisions taken in cases of disciplinary violations; categories of disciplinary violations; sanctions provided. The article is intended to initiate further discussion about these matters among scientists, practitioners, and the general public, not just in Lithuania but in other countries as well.